The Influence of the Distribution Characteristics of Complex Natural Fracture on the Hydraulic Fracture Propagation Morphology - Zhao, Huan; Li, Wei; Wang, Lei; Fu, Jing; Xue, Yun Long; Zhu, Jian Jun; Li, Si Qi (Frontiers in Earth Science, 2022)
Natural fractures are common in unconventional reservoirs (e.g., tight oil and gas, shale oil and gas), for which hydraulic fracturing is the main exploitation method. Natural fractures influence the propagation and final transformation effect of hydraulic fractures, which is an important factor for fracture optimization design. In this work, the method of globally embedding zero-thickness cohesive zone elements is applied to establish a dynamic propagation model of hydraulic fractures in naturally fractured reservoirs, and the influence of natural fracture development on the fracture propagation patterns is investigated. The results show that the hydraulic fracture propagation paths in fractured reservoirs are highly complex, and steering, branching, and merging of the propagation paths may occur. When the natural fracture development is small, the fracture propagation pattern is mainly influenced by the minimum horizontal principal stress. In contrast, when the natural fracture development is large, the fracture propagation pattern is influenced by the natural fracture distribution. With increasing natural fracture angle, hydraulic fractures can easily pass through natural fractures and form wide fracturs. Higher numbers of natural fracture groups and fractal dimensions increase the number of fracture propagation directions and communicating natural fractures, and the fractures tend to be narrow and complex.